Media Augmented Reality Berbasis Android Pada Materi Sistem Pencernaan untuk Kelas XI SMA/MA - Atirah; Ainul Uyuni Taufiq; Wahyuni Ismail (Al-AHYA: Jurnal Pendidikan Biologi, 2022)
This study aims to (1) develop Augmented Reality learning media on the digestive system material for class XI SMAN 8 Soppeng, (2) determine the level of validity of Augmented Reality learning media on the digestive system material for class XI SMAN 8 Soppeng, (3) determine the level of practicality of Augmented learning media. Reality on the digestive system material for class XI SMAN 8 Soppeng, (4) knowing the effectiveness of Augmented Reality learning media on the digestive system material for class XI SMAN 8 Soppeng. The research method is research and development (R & D) with a 4-D development model, namely define, design, develop and disseminate. The results showed that Augmented Reality learning media on the digestive system material developed had a validity level by a material expert team and a valid design expert team, namely 3.68, the assessment of student responses and educator responses, the practicality level was in the practical category with an average total score of 3.64. The test of student learning outcomes using Augmented Reality learning media is categorized as effective because it reaches 100%. So that Augmented Reality learning media is feasible to use because it has met the valid, practical and effective criteria.